Pengaruh Profitabilitas, Leverage dan Ukuran Perusahaan terhadap Penghindaran Pajak pada Perusahaan Manufaktur yang Terdaftar di BEI pada Tahun 2019-2021 - Faradita, Fadilah Huriyah; Muhammad, Maulana Malik (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
This research is aimed at examining the effect of Profitability, Leverage, and Size on Tax Avoidance in manufacturing companies listed on the Indonesia Stock Exchange. The population in this research are manufacturing companies listed on the IDX during the 2019 – 2021 period. The sample in this research was 36 manufacturing companies which were determined based on the purposive sampling method. Methods of data analysis using panel data regression using Eviews 12 software. The test results show that partially profitability, leverage and company size have a negative and insignificant effect on avoidance. And simultaneously, profitability, leverage and company size have no influence on tax avoidance.